PENGARUH RETURN ON ASSET, CURRENT RATIO, SIZE DAN GROWTH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 - 2015 - Lina, .; Amir, Afriza (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
This study aims to test and analyze the effect of Return on Asset, Current Ratio, Size and Growth on Capital Structure in manufacturing company listing in Indonesia Stock Exchange in years 2013 - 2015. In this Research there is 151 population of manufacturing company listing in Indonesia Stock Exchange in years 2013 - 2015. The sample of this research amounted to 183 financial reports from 61 manufacturing companies listing in Indonesia Stock Exchange in years 2013 - 2015. The test results which are the research conclusions are Return on Asset and Current Ratio partially shows negative affect and significant toward Capital Structure in manufacturing company listing in Indonesia Stock Exchange in years 2013 - 2015. Size and Growth no affect toward Capital Structure in manufacturing company listing in Indonesia Stock Exchange in years 2013 - 2015.Return on Asset, Current Ratio, Size dan Growth simultaneously showsaffect and significant the Capital Structure in manufacturing company listing in Indonesia Stock Exchange in years 2013 - 2015.Keywords : Return on Asset, Current Ratio, Size, Growth and Capital Structure